The Military Orders and Women of the Nobility in the Crusader States - Burgtorf, Jochen (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2023)
To assess the interaction between the military orders and women of the nobility in the Crusader states neither the narrative sources’ scattered anecdotes nor the normative texts’ stipulations pertaining to women are particularly useful or representative. Focusing on the kingdom of Jerusalem and, to a lesser extent, the principality of Antioch and the county of Tripoli in the twelfth and thirteenth centuries, this article considers examples from the charter evidence to appreciate the impact of queens, princesses, countesses, and noble ladies on the history of Templars, Hospitallers, and Teutonic Knights. The first part highlights the significance of consent-giving; the second part takes a closer look at activities where ladies functioned as primary agents, namely, as issuers of charters; and the third part presents a case study of Lady Juliana of Caesarea ‒ a benefactress of both Hospitallers and Teutonic Knights in the late twelfth and early thirteenth centuries ‒ whose husbands (despite their dominus/“lord” titles) only participated in the administration of her lordship iure uxoris (i.e., on the basis of Juliana’s legal title); who became a consoror (i.e., a “fellow sister”) and chose the Hospital of St. John as her final resting place; and whose second husband, Aymar of L’Ayron, later joined the Hospitallers and served as their conventual marshal during the Crusade against Damietta.